2006
DOI: 10.1159/000094916
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Outcome of Percutaneous Transluminal Renal Angioplasty in Patients with Renal Failure

Abstract: Background: The indications for percutaneous transluminal renal angioplasty (PTRA) in renovascular disease, as well as its benefits, remain a matter of debate. The aim of this study was to evaluate the outcome of angioplasty and to identify risk factors associated with less successful outcomes in patients with atheromatous renal artery stenosis and renal failure of varying degrees. Methods: The results of PTRA were analyzed retrospectively in 144 patients with serum creatinine levels of >130 µmol/l. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Other studies have similarly demonstrated that serum creatinine values can be used to predict improvement in renal function following PTRA [124, 125]. Furthermore, ARAS patients undergoing PTRA with creatinine values >300 µmol/l (3.9 mg/dl) have almost 5-fold higher mortality rates compared with patients with creatinine values <300 µmol/l (relative risk = 4.7, 95% CI = 2.0–11.0, p < 0.0005) [126]. …”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Other studies have similarly demonstrated that serum creatinine values can be used to predict improvement in renal function following PTRA [124, 125]. Furthermore, ARAS patients undergoing PTRA with creatinine values >300 µmol/l (3.9 mg/dl) have almost 5-fold higher mortality rates compared with patients with creatinine values <300 µmol/l (relative risk = 4.7, 95% CI = 2.0–11.0, p < 0.0005) [126]. …”
Section: Literature Search Resultsmentioning
confidence: 99%
“…A favorable outcome was correlated with a lower creatinine level (P = 0.0137) and a more rapid prior loss of renal function (r = 0.49, P = 0.020) at entry. Roussos et al [33] showed that patients with ARAS who were referred for angioplasty because of deteriorating renal function (mean serum creatinine: 3.66 ± 1.89 mg/dL) had a small increase in glomerular filtration rate at 3-month follow-up (from 23 ± 11 to 27 ± 14 mL/ min/1.73 m 2 ; P = 0.021). Analysis with patients who had both renal function deterioration and accelerated hypertension showed improvement of glomerular filtration rate (from 25 ± 11 to 28 ± 14 mL/min/1.73 m 2 ; P = 0.031) 3 months after intervention.…”
Section: Ptra: Effects On Renal Functionmentioning
confidence: 99%
“…1,2 During follow-up, most stent-related complications are restenosis. Only a few cases of renal stent fractures have been reported in the relevant literature.…”
mentioning
confidence: 99%